SYNERGY OF PANCASILA AND POLITICS ON ECOLOGICAL CIVIC EDUCATION IN PUAY VILLAGE, PAPUA PROVINCE - Ode Jamal; Ade Sopyan Hadi; Maya Mashita; Nesliani Paotonan; Grand Barrang; Melianan Refasi Refas (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
In Indonesia, various disasters frequently occur, and in many cases, they are not solely caused by natural factors, but also by irresponsible human behavior and activities regarding the environment. These disasters include floods caused by illegal logging and indiscriminate waste disposal that clog waterways; forest fires often caused by land clearing by burning; and river pollution caused by untreated household and industrial waste. These conditions demonstrate that human behavior plays a significant role in exacerbating environmental damage and increasing the risk of disasters in various regions of Indonesia. The purpose of this study is to show data regarding the Synergy of Pancasila and Politics on Ecological Citizenship Education in Puay Village, Papua Province. The research method used in this study is a qualitative approach, while the type of research used is a case study. The results of this study show data that efforts to protect the environment which is part of the ecological citizenship carried out by the Puay Village community are by planting trees, cleaning the banks of Lake Sentani in Puay Village when commemorating the entry of the Gospel in Puay Village, and introducing the nature around Lake Sentani to students of SDN 5 Puay Village. The conclusion of this study is that the Puay Village community has contributed to protecting nature, especially the environment around Lake Sentani, which is the lifeblood of the Puay Village community.